Family-Centered Early Intervention to Support Communication Development in Children with Multiple Disabilities with Visual Impairment - Citra Ashri Maulidina; Lintang Al-mar’atus Sholihah; Mohammad Arif Taboer; Kholifatul Novita Ningsih (GRAB KIDS: Journal of Special Education Need, 2026)
This study aims to formulate an early intervention program based on family resources for parents to stimulate communication of MDVI children at home. This research was motivated by a lack of understanding of families in providing intervention efforts to optimize communication skills in children with MDVI from an early age. The subjects in this study were two parents who had MDVI children. The first subject was the family of a child with early AZs who had a visual impairment with autism. The second subject was the family of a child with an early K who had visual impairment and hearing loss.  This research approach is a qualitative approach with three stages of research, namely assessment, validation, and implementation. The result of this study is that parents know the characteristics and needs of their children, there is a positive acceptance from parents, and parents begin to know the communication principles of MDVI children and begin to practice them in a way that directly positively affects the  child's communication.